(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2024)
Today’s construction businesses have been characterized by the use of science and technology in operation and huge competitiveness resulting from the effect of globalization that has necessitated a free business market environment beyond borders. The situation has forced even local construction firms to struggle to find an alternative to reduce the increasingly overwhelming challenges resulting from increased client demands and desires. The bullwhip effect is among the identified challenges that affect supply chain management throughout the construction projects. The Bullwhip effect is the phenomenon that shows how the small changes at the demand end of a supply chain are progressively amplified for operations further back in the chain. As a result, this study aims to investigate the impact of bullwhip effects on construction projects and supply chain performance. Eighty (82) respondents were randomly selected from road construction projects in Tanzania, where the supply chain is well practiced. Data were collected using a semi-structured questionnaire and descriptively analyzed using Statistical Package for Social Science (SPSS-24) to obtain the statistical information presented using descriptive information such as frequencies and percentages. The study's findings have identified nine bullwhip effect causes and eleven bullwhip effects that significantly and positively influence the supply chain performance of construction projects. Therefore, the findings recommend that the bullwhip effects, which pose challenges to both the construction firm and the sector as a whole, should not be ignored. However, the study suggests that further research is necessary to determine the role, necessity, and impact of technology within a construction supply chain, particularly in terms of its potential to mitigate the bullwhip effect.